The Behavior of Slab-Column Connections with Modified Shear Reinforcement under Cyclic Load - Gunadi, Riawan; Budiono, Bambang; Imran, Iswandi; Sofwan, Ananta (Journal of Engineering and Technological Sciences, 2014)
Generally, slab-column frames show lower stiffness, drift capacity, and ductility as compared to beam-column frames. Under combined gravity and lateral cyclic loading, the lower initial stiffness and stiffness degradation lead to poor structural performance. Therefore, in the current codes, slab-column frames are recommended only for Intermediate Moment Frames with dual systems. The objective of this study is to modify slab-column connection details to enhance seismic performance such that the system can also be used with Special Moment Frames. Four specimens of interior slab-column connection models with the same dimensions and flexural reinforcement were tested under gravity and cyclic lateral loads. One specimen, constructed as control specimen, was designed using standard orthogonal stud rails. The other specimens used newly designed stud rails. The experimental results demonstrated that the modified stud rails significantly improved the specimensâ behavior. The experimental results demonstrated that the modified stud rails significantly improve the specimen behavior. The highest ratio of initial stiffness adequacy of specimen with modified stud rail was 131.19% for risk category I/II, while the ratio of the control specimen was 97.94%. The highest relative energy dissipation ratio of specimen with modified stud rail was 33.82%, while the ratio of the control specimen was 25.94%.